Characterization of 2450‐MHz microwave thermal coagulation zone based on characteristic length growth model and shape variation factor. Issue 6 (12th March 2019) - Gao, Hongjian; Wang, Xiaoru; Wu, Shuicai; Zhou, Zhuhuang; Bai, Yanping; Ai, Haiming
Abstract: It is critical for microwave ablation (MWA) treatment planning to evaluate the changes of thermal coagulation zones. In MWA procedures, the shapes and sizes of thermal coagulation zones are gradually evolving over time. To this end, a novel characterization and mapping method of thermal coagulation zones is presented in this article. Firstly, finite element method (FEM) models of temperature distributions for 40, 45, 50, 55, and 60 W microwave ablations were built to derive thermal ablation data of ex vivo porcine livers and were compared with experimental results. Secondly, growth models of characteristic lengths were fitted. Finally, characterization functions of thermal coagulation zones were developed using these growth models. In addition, shape variation factors were incorporated to handle the minor shape variations of thermal coagulation zones. Experimental results showed that these characterization functions could accurately represent the changes of thermal coagulation zones. The standard deviations between prediction results and simulated values were less than 1 mm. The comparative results were statistically analyzed by paired t test ( P  > 0.05), indicating no significant differences. The proposed method can simply and effectively predict the changes of MWA coagulation zones with time, thus providing reliable coagulation dimensions for the thermal ablation therapies.